THE IMPLEMENTATION OF GOOD GOVERNANCE IN REGIONAL FINANCIAL MANAGEMENT IN SOUTH CENTRAL TIMOR REGENCY - Ludji, Priska Trivena Regina; Tungga, Cicilia A.; Molidya, Aldarine (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to analyze the implementation of good governance principles—namely transparency, accountability, and public participation—in regional financial management in South Central Timor Regency. The method used is descriptive qualitative, with data collection techniques including interviews, documentation, and analysis using NVivo software. The findings indicate that the local government has made efforts to implement transparency through digital information systems and public information dissemination, although challenges remain, such as the limited use of social media. Accountability is pursued through internal audits and the publication of financial reports, but there are still issues concerning the effectiveness of oversight. Public participation in budget management remains largely formal and has yet to become fully participatory. The study concludes that the application of good governance principles in South Central Timor Regency is underway but still requires strengthening, particularly in implementation and community involvement, to achieve better and more sustainable governance.